1999
DOI: 10.1074/jbc.274.14.9175
|View full text |Cite
|
Sign up to set email alerts
|

Barley BLZ2, a Seed-specific bZIP Protein That Interacts with BLZ1 in Vivo and Activates Transcription from the GCN4-like motif of B-hordein Promoters in Barley Endosperm

Abstract: A barley endosperm cDNA, encoding a DNA-binding protein of the bZIP class of transcription factors, BLZ2, has been characterized. The Blz2 mRNA expression is restricted to the endosperm, where it precedes that of the hordein genes. BLZ2, expressed in bacteria, binds specifically to the GCN4-like motif (GLM; 5-GTGAGT-CAT-3) in a 43-base pair oligonucleotide derived from the promoter region of a Hor-2 gene (B1-hordein). This oligonucleotide also includes the prolamin box (PB; 5-TGTAAAG-3). Binding by BLZ2 is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
126
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 47 publications
8
126
0
4
Order By: Relevance
“…GLM is an essential positive element for the endosperm-specific gene expression. Oñate et al (1999) demonstrated that BLZ2, the bZIP class of transcription factors, binded specifically to the GLM motif (5 0 -GTGAGTCAT-3 0 ) in the promoter region of a B1-hordein gene. Binding by BLZ2 is prevented when the GLM mutated to 5 0 -GTGctTCtc-3 0 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GLM is an essential positive element for the endosperm-specific gene expression. Oñate et al (1999) demonstrated that BLZ2, the bZIP class of transcription factors, binded specifically to the GLM motif (5 0 -GTGAGTCAT-3 0 ) in the promoter region of a B1-hordein gene. Binding by BLZ2 is prevented when the GLM mutated to 5 0 -GTGctTCtc-3 0 .…”
Section: Discussionmentioning
confidence: 99%
“…The EB box contained two distinct nuclear protein binding sites: the prolamin box (PB, 5 0 -TGTAAAG-3 0 ) also referred to as the endosperm motif (EM), and a GCN4-like motif (GLM, 5 0 -(G/A)TGA(G/C)TCA(T/C)-3 0 ). These two motifs are present in B-and C-hordein promoters (Oñate et al 1999). The Dof class of transcription factors can bind specifically to EM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An understanding of gene expression control in the seed was tackled from early studies in plant molecular biology, with maize (Zea mays) Opaque2 (O2) representing a hallmark as one of the first plant transcription factor (TF) genes cloned and characterized (Hartings et al, 1989;Schmidt et al, 1990). Similarly, orthologous genes from wheat (Triticum aestivum) (SPA) and barley (Hordeum vulgare) (BLZ2) play the same roles as O2 in their corresponding species (Albani et al, 1997;Oñ ate et al, 1999). In dicot species, key TFs have been characterized that control gene expression programs during seed maturation.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro DNase I footprinting with nuclear proteins from rice maturing seeds and GST-O2 fusion protein also showed that the sequence covering the GCN4 motif in the promoter of glutelin genes is specifically protected from DNase I digestion (8,17). These findings suggest that O2-like transcription factor may exist and participate in controlling the endosperm-specific expression of many storage protein genes in cereal seed through the GCN4 motif.The cDNA clones encoding transcription factor recognizing the GCN4 motif have been recently isolated and characterized in wheat (5) and barley (18,19). These transcription factors, designated SPA, BLZ1, and BLZ2, transcriptionally activate expression of the storage protein genes by interacting with the GCN4 motif in the wheat low molecular weight glutenin and barley B1-hordein promoters.…”
mentioning
confidence: 99%